Mathematical Communication Based on Maslow's Theory: A Study of Learning Motivation in Elementary School Students - Hardiyanto, Ryan; Salsabila, Zahira (Papanda Publisher, 2023)
Mathematical communication skills are of utmost importance for students to effectively solve mathematical problems. However, the evidence suggests that elementary school students still exhibit very low levels of communication skills. Communication skills are influenced significantly by various factors, and one of these factors is learning motivation. This study aims to describe and analyze the mathematical communication abilities of students in the topic of linear equations of two variables, taking into account their learning motivation based on Maslow's theory. The research design employed in this study is descriptive qualitative. The data collection instruments consist of written tests on the topic of a two-variable linear equation system, non-test instruments in the form of questionnaires to assess students' learning motivation based on Maslow's theory, and semi-structured interview guidelines. The subjects of the study were fifth-grade students at SDN Kedungsari Purwerejo, and a sample of six students was selected using purposive sampling. The data analysis technique involved data reduction, data visualization, and drawing conclusions. The research findings indicate that students who fulfill all aspects of Maslow's theoretical hierarchy exhibit higher learning motivation. This is evident in the differences observed in their responses to the questions. Students who fulfill all aspects of Maslow's theoretical hierarchy put in more effort to provide detailed and clear answers, while students who only fulfill some aspects of Maslow's theoretical hierarchy tend to answer questions more straightforwardly without providing a more elaborate explanation.